Preliminary study of transport pattern and demand in Singapore for future urban air mobility - Wai, Cho Wing (2021)
This paper aims to present the preliminary feasibility study of future urban air mobility (UAM), by means of flying taxis, based on the existing transportationdemands in Singapore. Some cities such as Dallas, Los Angeles and Melbourne have already investigated the trends of urban air mobility and planned to launch its eVTOL in 2023. The consideration behind flying taxis in Singapore serves to smoothen traffic congestions in the central and industrial areas due to occasional traffic jams caused by road works or accidents, providing greater transportation convenience in a cosmopolitan city. Firstly, the research focused on the demand in terms of cost, travel time and the travel distance for various modes of conventional transport across Singapore. Eight reference mission scenarios were analysed in line with real-time traffic and fare-time patterns were studied to understand how passengers could benefit from it, in terms of time and cost savings. Secondly, the research was narrowed down to the Central Business District (CBD) and focused on tourists’ transport demands using statistics provided by the Singapore Tourism Board (STB). The goal is to determine which districts had the most in-demand and how tourists could benefit by taking a flying taxi. The objective of this preliminary study is also to gather baseline data so as to further investigate on whether flying taxis in Singapore is viable and determine how to optimise that from different perspectives of various stakeholders, including the efficiency of flying taxis.